Q: Simplify -5r-9s plus 9r plus 3s-6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Combine the ' 9r ' and the ' -5r ' . Replace them with ' 4r '.

-9r plus 10r can be written as ( -9r + 10r) and the answer is r.

3+10-r+6r = -3+9r+0 13+5r = -3+9r 16 = 4r r = 4

9r-1?

9-4r

Related questions

Combine the ' 9r ' and the ' -5r ' . Replace them with ' 4r '.

-9r plus 10r can be written as ( -9r + 10r) and the answer is r.

Cant do much with this one.9r-4s / 9r+6s9r-4s / 3(3r+2s)

3+10-r+6r = -3+9r+0 13+5r = -3+9r 16 = 4r r = 4

It is 5n + 9r.

9r-1?

9-4r

-9r = 20 + rsubtract r from both sides-10r = 20divide both sides by -10r = -2

3(g + 6b + 3r)

16r2+9r

9r = 3r + 6 subtract 3r from both sides 6r = 6 divide both sides by 6 r=1 ■

83-9r = 74